Do coupled subsidies increase milk productivity, land use, herd size and income? Evidence from Kosovo - Egzon Bajrami; Eric J. Wailes; Bruce L. Dixon; Arben Musliu; Alvaro Durand-Morat (Studies in Agricultural Economics, 2019)
This study assesses the effectiveness of the Subsidy per Head Scheme (SPHS) in increasing milk productivity, land use, herd size and income in dairy farms across the seven regions of Kosovo. SPHS represents one of the largest coupled subsidy programs in the agricultural sector of Kosovo in terms of farmer participation and budget allocation. We use a Propensity Score Matching approach to assess the impact of this program by comparing a group of participants with a group of non-participants during the 2013–2014 farming seasons. We test the robustness of the impact results using four different matching algorithms. Results reveal SPHS was not effective in increasing land use, gross income and farm size (number of cows), although SPHS had a limited impact on improving milk productivity. In addition, the study highlights the need to reformulate coupled subsidies and develop new, complementary strategies that address farmers' needs more efficiently.
Keywords: Q18; 330; coupled subsidy; propensity score matching; impact evaluation; Kosovo